Agama dan Kemajuan Teknologi Digital: Digital Religion dan Media Sosial - Najiha, Rina (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
The development of digital technology has globally transformed religious practices, including in Indonesia, by creating a hybrid space between online and offline activities known as digital religion. This study aims to analyze how the transformation of religious practices through social media affects the understanding, practice, and religious identity, particularly among young Indonesian Muslims. Using a literature review method and qualitative content analysis, this research examines various theoretical and empirical references related to digital religion, employing a conceptual framework that integrates the theories of networked religion (Campbell) and mediatization (Hjarvard). The findings show that social media has become a key platform in transforming religious practices, giving rise to new forms of religious authority such as